Radiation-Induced Intraspinal Chondrosarcoma: A Case Report - Obid, Peter (Global Spine J, 2015)
Study Design Case report and review of the literature. Objective To report a unique case of an intraspinal chondrosarcoma that was diagnosed 18 years after radiotherapy for a cervical carcinoma and its remarkably unusual clinical presentation. Methods A retrospective case description of an intraspinal mass lesion that occurred 6 weeks after previous spinal surgery. Results Within ∼9 weeks, the tumor had infiltrated the peritoneal cavity and reached the lumbar subcutaneous tissue. Conclusion Radiation-induced sarcomas are rare, are highly aggressive, and may be difficult to diagnose. Furthermore, the only means of achieving long-term survival is through early and extensive surgery.